Synthesis, Spectroscopic and Antibacterial Studies of N(2-amino phenyl)-N-((pyridine-2-yl)methyl)Benzene-1,2-Diamine Complexes - Naji, Shaymaa H (Al-Nahrain Journal of Science, 2018)
N(2-amino phenyl)-N-((pyridine-2-yl)methyl) benzene-1,2-diamine (L) was prepared from the reaction of ortho amino phyenylthiol with N(2-amino methyl pyridyl) phenyl diamine in mole ratio (1:1). It was characterized by elemental analysis (CHN),1H, 13C-NMR, IR and Uv-Vis. The complexes of the bivalent inos (Co (II), Ni (II), Cu (II), Pd (II), Cd (II) and Hg (II)) and the trivalent (Cr (III)) have been prepared and characterized too. The structural were established by elemental analysis (CHN), IR, Uv-Vis spectra, conductivity measurements, atomic absorption and magnetic susceptibility. The complexes showed characteristic behavior of octahedral geometry around the metal ions except with Cu and Pd complexes showed square planer, other parameters for complexes were estimated. The study of biological activity of the ligand (L) and its metal complexes showed various activity toward staphylococcus aureus and E. coli.